Oral Mucormycosis and Aspergillosis in the Patient with Acute Leukemia - Vučićević Boras, Vanja (Acta Stomatol Croat, 2019)
A 54-year-old male patient with acute lymphoblastic leukemia was referred to the Department of Oral Medicine. He had a primary refractory disease and was treated according to HOVON71 and HAM protocol. Sixteen days after the start of the HAM protocol the patient developed palatal dark red/brownish lesion and maxillary vestibular exophytic lesion. Biopsy specimens from oral lesions were taken and microbiologic evaluation confirmed the presence of Aspergillus fumigatus and Rhizopus genus. The treatment of the patient consisted of the inferior maxillectomy and intravenous posaconazole and amphotericine B for the following 28 days. Since the coinfection with Aspergillus and Rhizopus is extremely rarely seen in the oral cavity, a diagnostic and therapeutic dilemma easily presents itself.